Ferroptosis in Rheumatoid Arthritis: A Potential Therapeutic Strategy - Zhao, Ting; Yang, Qi; Xi, Yujiang; Xie, Zhaohu; Shen, Jiayan; Li, Zhenmin; Li, Zhaofu; Qin, Dongdong (Frontiers in Immunology, 2022)
Ferroptosis is one of the newly discovered forms of cell-regulated death characterized by iron-dependent lipid peroxidation. Extensive research has focused on the roles of ferroptosis in tumors, blood diseases, and neurological diseases. Some recent findings have indicated that ferroptosis may also be related to the occurrence and development of inflammatory arthritis. Ferroptosis may be a potential therapeutic target, and few studies in vitro and animal models have shown implications in the pathogenesis of inflammatory arthritis. This mini review discussed the common features between ferroptosis and the pathogenesis of rheumatoid arthritis (RA), and evaluated therapeutic applications of ferroptosis regulators in preclinical and clinical research. Some critical issues worth paying attention to were also raised to guide future research efforts.